Enhancing Teacher Competence in Inclusive Early Childhood Education: An Action Research Study on Project-Based Teaching Implementation - Solihati, Iis; Hermanto, Hermanto (Journal of Innovation and Research in Primary Education, 2025)
Inclusive early childhood education faces significant challenges in effectively managing classrooms where children with diverse abilities and developmental needs learn together. Traditional teacher training approaches remain predominantly theoretical, creating substantial gaps between policy mandates and practical implementation. This study investigated how project-based teaching implementation enhances kindergarten teachers' competence in inclusive classroom management through systematic professional development intervention. A qualitative action research design was employed across three kindergarten institutions in Kongbeng District, East Kutai Regency, Indonesia, from March to June 2025. The study utilized a cyclical approach involving planning, implementation, observation, and reflection phases. Data collection employed structured interviews, passive participant observation using five-point Likert scale instruments, and documentary analysis. Twelve indicators assessed project-based teaching implementation, teacher competence (pedagogical, professional, social, and personality dimensions), and inclusive classroom management capabilities. Data validity was ensured through source and technique triangulation. Substantial improvements in teacher competence were observed across all institutions, with performance increases ranging from 30% to 33.34% compared to baseline measurements. Pre-intervention scores of 60-63.33% (moderate competence) improved to 90-96.67% (very high competence) by Cycle II. Teachers demonstrated enhanced abilities in project planning, facilitating collaborative learning, adapting materials for special needs children, and implementing inclusive evaluation strategies. Qualitative feedback revealed increased confidence and pedagogical effectiveness. Project-based teaching significantly enhances teacher competence in inclusive classroom management through structured professional development combining theoretical learning with practical implementation. The cyclical intervention approach proves effective in bridging theory-practice gaps, offering a practical framework for inclusive education implementation in early childhood settings.